PIROLISIS MIKROALGA Spirulina platensis MENGGUNAKAN THERMOGRAVIMETRIC ANALYZER DENGAN LAJU PEMANASAN 20℃/MENIT - Madani, Nabila Mutiara; Subagyono, RR. Dirgarini Julia Nurlianti; Kassim, Mohd. Asyraf (PROSIDING SEMINAR KIMIA, 2024)
Pyrolysis of microalgae Spirulina platensis using a thermogravimetric analyzer with a heating rate of 20℃/min was carried out. The thermal decomposition pattern and temperature range of active and passive pyrolysis of Spirulina platensis pyrolysis are the focus of this study. Based on the analysis, the water content and ash content of green microalgae Spirulina platensis were 8.34% and 7.18%. The decomposition pattern in Spirulina platensis pyrolysis is divided into three stages, namely water evaporation occurs at temperatures ≤ 150 ℃, the main devolatilization stage or active pyrolysis occurs in the temperature range 155 - 536 ℃ and the passive pyrolysis stage occurs at temperatures ≥ 536 ℃. Keywords: Spirulina platensis, Pyrolysis, and Thermogravimetric Analysis.